2017
DOI: 10.1186/s12935-017-0430-x
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of endothelial cell migration by tumor associated macrophage-derived exosomes is reversed by epithelial ovarian cancer exosomal lncRNA

Abstract: ObjectiveTo study the mechanism by which epithelial ovarian cancer (EOC)-derived exosomes restore the migration of endothelial cells that is suppressed by TAM-derived exosomes.MethodsExosomes were isolated from TAMs in the ascites of patients with EOC. The effect of exosomes on the expression of endothelial cell miRNA was monitored by PCR. The miRNA mimics were transfected to explore their effects. Microarray data and literature searches were used to predict target genes and the impact of target gene pathways,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 27 publications
0
61
0
Order By: Relevance
“…Exosomes potentially promote the malignancy of tumor cells by transferring oncogenic lncRNAs to induce tumor formation and metastasis [36]. Exosomal LncRNAs are transcribed to regulate the expression of oncogenes and tumor suppressor genes in tissue-and cell-specific manners [17].…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes potentially promote the malignancy of tumor cells by transferring oncogenic lncRNAs to induce tumor formation and metastasis [36]. Exosomal LncRNAs are transcribed to regulate the expression of oncogenes and tumor suppressor genes in tissue-and cell-specific manners [17].…”
Section: Discussionmentioning
confidence: 99%
“…TRAF6 is a member of the TNF receptor–associated factor (TRAF) family . Recent studies have shown that inhibition of the TRAF6/NF‐κB/MMP2 pathway can affect endothelial cell invasion and migration . Studies have also shown that inhibition of the AT1R‐NFκB‐TRAF6‐mitogen‐activated protein kinase (MAPK) pathway affects endothelial cell proliferation and vascular regeneration .…”
Section: Discussionmentioning
confidence: 99%
“…32 Recent studies have shown that inhibition of the TRAF6/NF-κB/MMP2 pathway can affect endothelial cell invasion and migration. 33 Studies have also shown that inhibition of the AT1R-NFκB-TRAF6-mitogen-activated protein kinase (MAPK) pathway affects endothelial cell proliferation and vascular regeneration. 34 These results may indicate that TRAF6 also plays an important role in endothelial cell proliferation, invasion and migration.…”
Section: Discussionmentioning
confidence: 99%
“…At a molecular level, the main target of IL-6 signalling is STAT3 which binds the lncTCF7 promoter sequence directly 67 A growing body of evidence suggests that EV derived lncRNAs are functional within the tumour microenvironment and may have important biological effects in recipient cells. [71][72][73] LncRNAs within EVs have also generated interest as diagnostic and/or prognostic biomarkers in cancer as specific lncRNAs appear to be enriched in EVs produced by cancer cells [74][75][76] and can be retrieved and reliably profiled from EV extracted from human bio-fluids. 77,78 Exosomes which are 30-100nm endosome derived vesicles appear to be the richest reservoir of lncRNA whilst the larger (100-100nm) plasma membrane derived MVs appear to contain the lowest amount.…”
Section: Immune Cellsmentioning
confidence: 99%
“…Wu et al, discovered however, that ovarian cancer cell derived exosomes overcome this inhibition and identified two lncRNAs (ENST00000444164 and ENST00000437683) which may contribute to this effect by regulating NF-kB phosphorylation. 71 In renal cancer, exposure of HUVEC cells to exosomes which contain high levels of lncARSR (lncRNA Activated in RCC with Sunitinib Resistance) exhibited a poor response to sunitinib in tubule retraction assays implying that drug resistance may be propagated by exosomal lncRNAs within the tumour microenvironment. 80 A recent study has also shown that lung cancer-derived exosomes inhibit the potential for mesenchymal stem cells (MSC) to terminally differentiate and are associated with widespread deregulation of lncRNA expression.…”
Section: Lncrnas and Tumour-stroma Signallingmentioning
confidence: 99%